CULTURE AND POST-MASSIVE COMMUNICATION: HYBRIDISM IN VERY POPULAR BRAZILIAN MUSIC AND THE MULTIPLE FUNCTIONS OF THE LISTENER - Montenegro, Tatiana Martins; Arazimo, Carlos Yander Aguiar; Mello, Anna Cecília Chaves Limongi de (Anagrama, 2020)
This article aims to promote reflections about the current scenario of very popular Brazilian music, its historical configuration and perspectives. Through bibliographic and documentary research, the mechanisms that contributed to an understanding of the legitimacy of national popular culture were investigated, with an emphasis on music and the impact of new technologies for the production and dissemination of artistic manifestations. From the notes raised, it is assessed that the contemporary Brazilian music scene is directly affected by technological and macro-environmental transformations and that the main characteristic of national music today is hybridism, given that it defines artists, songs, style , the public and the communication channels used to practice this cultural event.